Modeling and Analysis of Carbon-Nanotube Interconnections for Future Nanotechnology Interconnections between High Speed CMOS Integrated Circuits using FDTD Method - Youssef Nadir; Hassan Belahrach; Abdelilah Ghammaz; Aze-eddine Naamane; Mohammed Radouani (E3S Web of Conferences, 2022)
The size reduction of copper interconnects degrades their performances due to increased surface scattering, which significantly reduces the effective electron mean free path. Unlike Cu, CNTs support ballistic electron flow with a lower value of mean free, which highly induces researchers to change copper by carbon nanotubes. In this way, this paper presents an accurate method based on the finite difference method describing the behavior of carbon nanotube interconnects in the time domain. The proposed algorithm is implemented in the MATLAB tool. The crosstalk between the interconnects and the induced delays are studied as a function of their length and the technology node (45nm, 32nm, 22nm and 16nm). The values obtained by the suggested method are compared with those of the PSPICE simulation tool. A good agreement between these results is observed, which demonstrates that CNT interconnects are more efficient than copper ones in terms of crosstalk induced delays.